Smooth return of UMP students following SOP - Mimi Rabita, Abdul Wahit (2021)
KUANTAN, 6 March 2021 - The process of returning to campus for Universiti Malaysia Pahang (UMP) students on 6 & 7 March 6 went smoothly when all students followed the standard operating procedures (SOP) after being given permission to return to the campus.